2021
DOI: 10.1063/5.0058704
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property correlations for analysis of heterogeneous electrocatalysts

Abstract: Heterogeneous electrocatalytic reactions are believed to occur at a minority of coordination sites through a series of elementary reactions that are balanced by minor equilibria. These features mask changes in reaction sites, making it challenging to directly identify and analyze reaction sites or intermediates while studying reaction mechanisms. Systematic perturbations of a reaction system often yield systematic changes in material properties and behavior. Correlations between measurable changes in parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 332 publications
0
12
0
Order By: Relevance
“…The importance of the structural distortion, or the oxygen vacancies associated with it, to electrocatalysis is evidenced by correlation between the average number of electrons transferred during ORR catalysis and the unit cell a dimension only for the Fe‐doped series (Figure 7D). Such changes in Tafel slope are often related to changes in reaction mechanisms [28–30] . The common assumption that the electron transfer coefficient (α) equals 0.5 yields only three possible Tafel slopes for accepted ORR mechanisms (120, 60 and 40 mV dec −1 ), but values ranging from 70 to 90 mV dec −1 have been reported for ORR [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the structural distortion, or the oxygen vacancies associated with it, to electrocatalysis is evidenced by correlation between the average number of electrons transferred during ORR catalysis and the unit cell a dimension only for the Fe‐doped series (Figure 7D). Such changes in Tafel slope are often related to changes in reaction mechanisms [28–30] . The common assumption that the electron transfer coefficient (α) equals 0.5 yields only three possible Tafel slopes for accepted ORR mechanisms (120, 60 and 40 mV dec −1 ), but values ranging from 70 to 90 mV dec −1 have been reported for ORR [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Such changes in Tafel slope are often related to changes in reaction mechanisms. [28][29][30] The common assumption that the electron transfer coefficient (α) equals 0.5 yields only three possible Tafel slopes for accepted ORR mechanisms (120, 60 and 40 mV dec À 1 ), but values ranging from 70 to 90 mV dec À 1 have been reported for ORR. [29] The relationships between B-site disorder and Tafel slope (Figure 7C) and reaction selectivity (Figure 7D) for an extended range leads us to propose that B-site distortions caused by Fe-doping changes α by selectively distorting the coordination environments of reaction sites.…”
Section: Discussionmentioning
confidence: 99%
“…Significant global efforts to develop improved catalysts in recent years have shown in operando structural changes and revealed that coordination environments other than those within the 2-dimensional bonding framework of Ni(OH) 2 are viable. 19 The electrochemical stability and catalytic activity of layered double hydroxide (LDH) materials is controlled by exsolution and redeposition mechanisms, where the stability of individual ions in specific coordination sites has been probed by analysis of surface coverage and adsorption energies. 20 It is well established that ferric ions are rapidly incorporated into LDH materials by simple exposure.…”
Section: Introductionmentioning
confidence: 99%
“…With such diversity in synthetic techniques, however, it is highly probable that variations in structural features exist that are hidden behind the abrupt changes in OER activity. Careful analysis of the changes in structure are necessary to identify any such variations, which can be accomplished through structure–property analysis …”
Section: Introductionmentioning
confidence: 99%
“…Careful analysis of the changes in structure are necessary to identify any such variations, which can be accomplished through structure−property analysis. 30 Efforts to identify individual coordination environments that are particularly active for electrocatalytic OER have revealed several specific structures that may be of importance. Undercoordinated ions residing along the edge, or at corners, of the layered double hydroxide structure are often viewed as the catalytically relevant sites.…”
Section: ■ Introductionmentioning
confidence: 99%